Design and Performance of Solar PV Integrated Domestic Vapor Absorption Refrigeration System - Divya Arputham Selvaraj; Kirubakaran Victor (International Journal of Photoenergy)
The arrival of new technologies has increased the energy demand day by day and does not seem to slow down at any time soon. High energy demand is adding risk on energy depletion and cause of various environmental issues. Air conditioner, chiller, and refrigerator occupy a considerable amount of the world’s total energy usage and have also proved to be a massive contributor to various environmental impacts. This technology might sound like a luxury on the surface, but they are in high demand to achieve food security. They can also help lifesaving vaccines to reach even the isolated parts of the world. Even though solar thermal refrigeration is a popular field, this paper solely concentrates on PV integrated refrigeration. In this paper, a renewable integration technology where a solar photovoltaic system is used to supply the electrical energy required to drive an absorption cycle is studied and compared with the commercial AC absorption refrigeration system. The Coefficient of Performance (COP) of the AC and DC system was 0.18 and 0.14. The simple payback of the system is 10.2 years.